Assessment of interdisciplinary competences in students of The Middle Education Pedagogy Program for Graduates and Graduates Andrés Bello University. - Riquelme Pérez, Nicole; Morales Flores, Nathaly; González Orb, Marcelo; Lobos-González, Manuel (PEM. Revista de Didáctica, Evaluación e Innovación, 2024)
Study aimed at assessing the interdisciplinary competencies of third semester students in the Secondary Education Pedagogy Program for Graduates and Graduates of the Andrés Bello University. Its design corresponds to quantitative, transversal and descriptive. The population is made up of the 23 university students of this training program. Data collection was carried out using the CETI, applied via Google Forms. The results show a generally positive perception of IC, highlighting a high valuation of the TCL and HI dimensions. On the other hand, opportunities for improvement in MII were identified. The results recommend strengthening interdisciplinary research methodologies, increasing group reinforcement activities, incorporating interdisciplinary case studies, and promoting integrative projects.